Risk Factors That Correlate with Resistance to First-Line Chemotherapy on High-risk Gestational Trophoblastic Neoplasia - Kurniadi, Andi; Zulvayanti, Zulvayanti; Suardi, Dodi; Mantilidewi, Kemala; Irsyad, Bayu Indrayana; Reswari, Arnova; Purwara, Benny Hasan; Winarno, Gatot Nyarumenteng Adhipurnawan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Gestational trophoblastic neoplasia (GTN) is a condition arising from abnormal proliferation of the trophoblastic cells. GTN incidence in Indonesia, precisely in Hasan Sadikin General Hospital, as many as 730 cases are reported per year. GTN is generally highly sensitive to chemotherapy, and multiagent chemotherapy regimens are recommended for high-risk GTN. Multiagent chemotherapy regimens for GTN treatment at Hasan Sadikin General Hospital are EMCO, with no other literature study describing chemotherapy resistance with EMCO today. AIM: This study aimed to identify risk factors associated with first-line chemotherapy resistance at Hasan Sadikin General Hospital. METHODS: In this cross-sectional study, medical records of 81 patients with high-risk GTN presented in the period from January 2018 to June 2021 who received EMCO chemotherapy at Hasan Sadikin General Hospital were retrieved from the archives, and medical data were reviewed and analyzed. Bivariate analysis was performed using the Chi-square test with Fisher’s exact alternative, and multivariate analysis using the binary logistic regression test. p < 0.05 was considered statistically significant. RESULTS: From 81 samples that received EMCO chemotherapy, 15 (18.5%) cases were resistant to EMCO, and 66 (81.5%) cases were responsive to EMCO. The risk factors associated with EMCO resistance were histopathological features and appropriate with EMCO chemotherapy interval (p < 0.05). Variables of age, previous pregnancy, GTN stage, FIGO prognostic score, stage, beta-hCG level, and side effects of EMCO did not significantly correlate with resistance to EMCO (p > 0.05). CONCLUSION: Histopathological features and appropriate chemotherapy intervals were associated with the incidence of resistance to EMCO in Hasan Sadikin General Hospital.